Candidate Genes Associated with Delayed Neuropsychomotor Development and Seizures in a Patient with Ring Chromosome 20 - Thiago Corrêa; Amanda Cristina Venâncio; Marcial Francis Galera; Mariluce Riegel (Case Reports in Genetics)
Ring chromosome 20 (r20) is characterized by intellectual impairment, behavioral disorders, and refractory epilepsy. We report a patient presenting nonmosaic ring chromosome 20 followed by duplication and deletion in 20q13.33 with seizures, delayed neuropsychomotor development and language, mild hypotonia, low weight gain, and cognitive deficit. Chromosomal microarray analysis (CMA) enabled us to restrict a chromosomal segment and thus integrate clinical and molecular data with systems biology. With this approach, we were able to identify candidate genes that may help to explain the consequences of deletions in 20q13.33. In our analysis, we observed five hubs (ARFGAP1, HELZ2, COL9A3, PTK6, and EEF1A2), seven bottlenecks (CHRNA4, ARFRP1, GID8, COL9A3, PTK6, ZBTB46, and SRMS), and two H-B nodes (PTK6 and COL9A3). The candidate genes may play an important role in the developmental delay and seizures observed in r20 patients. Gene ontology included microtubule-based movement, nucleosome assembly, DNA repair, and cholinergic synaptic transmission. Defects in these bioprocesses are associated with the development of neurological diseases, intellectual disability, neuropathies, and seizures. Therefore, in this study, we can explore molecular cytogenetic data, identify proteins through network analysis of protein-protein interactions, and identify new candidate genes associated with the main clinical findings in patients with 20q13.33 deletions.